Research of dispersion characteristics of optical glass - A.I. Yurin; G.N. Vishnyakov; V.L. Minaev (Компьютерная оптика)
Dispersion characteristics of optical glass are considered. An approach to research of dispersion characteristics of optical glass is proposed, requiring the measurement of the refractive index at only three wavelengths, which simplifies the measurement process compared with the use of the widely used Sellmeier equation. An approximation function for the refractive index of optical glass is proposed, the approximation error for various glass grades is calculated, and a method for correcting the approximation error is proposed. The refractive index measurements of optical glass samples are carried out at 3 wavelengths of He-Ne and Ar-Cr lasers, and values of the refractive index for spectral lines necessary for determining the dispersion characteristics are calculated. The value of the error in calculating the refractive index does not exceed ±1×10-5, which proves the prospect of using the proposed approximating function for studying the dispersion characteristics of optical glass.